2020
DOI: 10.1002/2211-5463.12805
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the key genes and microRNAs in prostate cancer bone metastasis by bioinformatics analysis

Abstract: Prostate adenocarcinoma (PCa) is the most common cause of death due to malignancy among men, and bone metastasis is the leading cause of mortality in patients with PCa. Therefore, identifying the causes and molecular mechanism of bone metastasis is important for early detection, diagnosis and personalized therapy. In this study, we systematically analyzed molecular correlates of bone metastasis by bioinformatics analysis. A total of 12 differentially expressed microRNAs (miRNAs) and 102 differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…Thus, messenger RNAs (mRNAs) that encode proteins were previously considered as the main study targets. 6 The expression of Myc-associated zinc-finger protein (MAZ) was found to be upregulated in PCa tissues with bone metastasis compared with those without bone metastasis. 7 High expression level of MAZ was positively correlated with poor overall and bone metastasis-free survival in PCa patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, messenger RNAs (mRNAs) that encode proteins were previously considered as the main study targets. 6 The expression of Myc-associated zinc-finger protein (MAZ) was found to be upregulated in PCa tissues with bone metastasis compared with those without bone metastasis. 7 High expression level of MAZ was positively correlated with poor overall and bone metastasis-free survival in PCa patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient group comparison at diagnosis based on their overall survival showed that miR-328, miR-671-3p, miR-636 and miR-363 are upregulated in relapsed patients. These miRs are described in the literature as promising prognostic biomarkers in AML or other malignant diseases [ 21 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Interestingly, all the patients involved in this comparison were not grafted, which suggests that these four miRs could constitute a signature to guide the choice of the best treatment strategy, especially the utility of grafting patients at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bii et al illustrated that MBNL2 was identi ed as a candidate gene in PCa progression [37] . Zhu et al demonstrated that miR-636 promotes cell invasion and migration, which might promote bone metastasis of PCa by targeting MBNL2 [38] . Taken together, we speculate that NOTCH1, GRIN1, STUB1, and MBNL2 contribute to the progression of CRPC.…”
Section: Discussionmentioning
confidence: 99%